Putative tumor suppressor gene SEL1L was downregulated by aberrantly upregulated hsa‐mir‐155 in human pancreatic ductal adenocarcinoma. Issue 9 (9th May 2013) - Liu, Qian; Chen, Jinyun; Wang, Jin; Amos, Christopher; Killary, Ann M.; Sen, Subrata; Wei, Chongjuan; Frazier, Marsha L.
Abstract Sel‐1‐like (SEL1L) is a putative tumor suppressor gene that is significantly downregulated in human pancreatic ductal adenocarcinoma (PDA). The mechanism of the downregulation is unclear. Here, we investigated whether aberrantly upregulated microRNAs (miRNAs) repressed the expression of SEL1L. From reported miRNA microarray studies on PDA and predicted miRNA targets, we identified seven aberrantly upregulated miRNAs that potentially target SEL1L. We assessed the expression levels of SEL1L mRNA and the seven miRNAs in human PDA tumors and normal adjacent tissues using real‐time quantitative polymerase chain reaction. Then statistical methods were applied to evaluate the association between SEL1L mRNA and the miRNAs. Furthermore, the interaction was explored by functional analysis, including luciferase assay and transient miRNA overexpression. SEL1L mRNA expression levels were found to correlate inversely with the expression of hsa‐mir‐143, hsa‐mir‐155, and hsa‐mir‐223 (P < 0.0001, P < 0.0001, and P = 0.002, respectively). As the number of these overexpressed miRNAs increased, SEL1L mRNA expression progressively decreased (Ptrend = 0.001). Functional analysis revealed that hsa‐mir‐155 acted as a suppressor of SEL1L in PDA cell lines. Our study combined statistical analysis with biological approaches to determine the relationships between several miRNAs and the SEL1L gene. The finding that the expression of the putative tumor suppressor SEL1L is repressed by upregulation of hsa‐mir‐155 helps to elucidate the mechanism for SEL1L downregulation in some human PDA cases. Our results suggest a role for specific miRNAs in the pathogenesis of PDA and indicate that miRNAs have potential as therapeutic targets for PDA. © 2014 Wiley Periodicals, Inc.